Some aspects of reproductive behaviour in Eucalyptus grandis (Hill) Maiden - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2024)
Thesis (DSc (Botany))--University of Pretoria, 1975.